Teaching Pilates for postural faults, illness, and injury : a practical guide - Paterson, Jane.; ScienceDirect eBooks (Edinburgh ; New York : Butterworth-Heinemann/Elsevier, 2009)
Pilates is a particularly safe and effective exercise system which aims to strengthen the body in a balanced way by specifically improving the function of the weaker muscle groups. Emphasis is placed on strengthening the muscles of the trunk so that support of the spine increases plus posture and shape improve. The exercises enhance overall flexibility and fitness, improving co-ordination and balance. Muscles are gently stretched and lengthened as the exercises progress and overall body strength improves. describes the underlying principles of the exercises in physical termsdescribes the treatment of common medical conditionsprovides a manual for those in the remedial health care professions.
Chapter 1 Good posture and how it can be achieved -- Introduction, -- Good erect posture, -- Postural faults, -- Useful tests, -- Tables of exercises for addressing postural faults -- Chapter 2 Common medical conditions and problems -- Eating disorders, -- Obesity, -- Chronic fatigue syndrome, -- Epilepsy, -- Multiple sclerosis, -- Parkinson`s disease, -- Diabetes mellitus, -- Thyroid disease, -- Osteoporosis, -- Osteoarthritis, -- Rheumatoid arthritis, -- Psoriatic arthritis, -- Gout, -- Hypertension, -- Coronary heart disease, -- Cerebrovascular disease, -- Chronic obstructive pulmonary disease, -- Asthma, -- Gastointestinal problems, -- Neck problems, -- Back problems, -- Hip problems, -- Knee problems, -- Lower leg problems, -- Ankle and foot problems -- Chapter 3 Anatomy review: torso, lower limbs and feet: -- Thoracic cage, -- Vertebral column, -- Pelvic girdle, -- Hip joint, -- Knee joint, -- Ankle joint and foot -- Chapter 4 Exercises for core stabilization and efficient movement: -- Prerequisite prepatory exercises, -- Basic core strengthening exercises -- Chapter 5 Anatomy review: the upper limb: -- Pectoral girdle, -- Elbow joint, -- Wrist joint -- Chapter 6 Upper body, stretching and overall joint mobilization exercises: -- Exercise list, -- Basic upper body exercises -- Stretching, joint mobilization and exercises to improve foot alignment, mobility and strength -- Chapter 7 The teaching process -- While the learner is doingthe exercise, -- Instruction, -- Further ways to improve your teaching -- Chapter 8 Health and safety -- Safe, effective prectice, -- The working space -- Appendix 1 Sample client record form -- -- Appendix 2 Sample postural assessment form -- Appendix 3 Suggested firther reading on anatomy.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Pilates method; HEALTH & FITNESS -- Healthy Living; HEALTH & FITNESS -- Holism; HEALTH & FITNESS -- Reference; MEDICAL -- Preventive Medicine; Pilates method; Exercise Movement Techniques -- methods; Electronic books